INTRODUCTION. (20th March 2014) - Unknown
Abstract : Lady Anne Bacon ( c .1528–1610) was a woman who inspired strong emotion in her own lifetime. As a girl, she was praised as a 'verteouse meyden' for her religious translations, while a rejected suitor condemned her as faithless as an ancient Greek temptress. The Spanish ambassador reported home that, as a married woman, she was a tiresomely learned lady, whereas her husband celebrated the time they spent reading classical literature together. During her widowhood, she was 'beloved' of the godly preachers surrounding her in Hertfordshire; Godfrey Goodman, later bishop of Gloucester, instead argued that she was 'little better than frantic in her age'. Anne's own letters allow a more balanced exploration of her life. An unusually large number are still extant; she is one of the select group of Elizabethan women whose surviving correspondence includes over fifty of the letters they wrote themselves, a group that incorporates her sister, Lady Elizabeth Russell, and the noblewoman Bess of Hardwick, the countess of Shrewsbury.